Harmony and Characterization in the Overture of Goca e Kaçanikut: A reflection on Kosovo’s Operatic Beginnings - Breznica, Rreze Kryeziu; Luzha, Besa (Harmonia: Journal of Arts Research and Education, 2025)
This paper examines the development of Albanian operatic creativity in Kosovo through a musicological analysis of Goca e Kaçanikut, the country’s first national opera. Employing a qualitative, score-based analytical approach, the study focuses on the overture as a structural and aesthetic gateway to the work, examining its form, harmonic language, orchestration, and incorporation of folk-derived elements. The findings demonstrate that harmony functions as a central expressive device in shaping character, dramatic tension, and narrative cohesion. At the same time, the integration of folkloric rhythmic and modal features contributes to the opera’s national character. The study highlights the overture as a condensed representation of Kosovo’s early operatic identity and argues that Goca e Kaçanikut establishes a foundational model for national opera within the broader European operatic tradition.